Epley versus Semont Maneuver in the Treatment of Benign Paroxysmal Positional Vertigo - Muthu, Aravind Karuppan; Bongale, Kiran Ravindranath; Bhat, Vikram Kemmannu (Annals of Otology and Neurotology, 2022)
Introduction Benign paroxysmal positional vertigo (BPPV) is characterized by brief but violent attacks of paroxysmal vertigo provoked by certain positions of the head. This study aimed to compare the outcomes of Epley and Semont maneuvers for the relief of vertigo in posterior semicircular canal BPPV.Materials and Methods This was a prospective comparative study conducted in a tertiary referral hospital over 1 year. Among 70 cases of BPPV, 35 were treated with Epley and 35 with Semont maneuver. Follow-up was done at 1 week, 1 month, and 3 months to assess symptomatic improvement using visual analogue scale.Results Out of 70 patients of BPPV, 62 patients responded very well to the maneuvers and got relief from vertigo. Thirty-two patients (91.4%) in the Epley group and 30 (85.7%) patients in the Semont group had a significant improvement post-therapy and the balance was the same in both groups. At 1 month, there was no significant statistical difference in mean visual analogue score (VAS) score between both groups.Conclusion Majority of cases showed symptomatic improvement with both maneuvers. However, patients treated with Epley maneuver showed earlier relief from vertigo than those treated with the Semont maneuver.
Keywords: BPPV; maneuver; posterior semicircular canal